Proteomic and enzymatic studies in relation to regeneration capacity of Boesenbergia rotunda cell suspension culture / Aiman Faizudin Aziz - Aziz, Aiman Faizudin (2018)
Gradual loss of cell proliferation and regeneration capacity in prolonged cultures of cell suspension continues to be a significant limitation, particularly those with economic interest and related studies. In this study, biochemical changes and proteins associated with cell proliferation and regeneration capacity from Boesenbergia rotunda cell suspension culture were investigated. The results showed that the optimum settle cell volume (SCV) of 6 and 9 month-old cell suspension proliferation were decreased of 42.17 % and 53.78 % respectively when compared to 0 month-old cells. In general, shoots of 4 ± 2 cm were formed after 7 months of culture. Regeneration response was recorded at 66.5 %, 56.6 %, and 47.4 % of 0, 6 and 9 month-old cells, respectively.